STUDY THE PERFORMANCE OF SULFAMIC ACID AND CITRIC ACID IN REMOVAL THE SCALE DEPOSITED ON THE DURA REFINERY HEAT EXCHANGE PIPING SYSTEM (Journal of Engineering, 2010)
This paper describes an experimental study on the performance of sulfamic acid and citric acid in scale removal of Dura refinery heat exchange piping systems. Experiments were carried out using sulfamic acid and citric acid inhibited by hexamine as cleaning solutions at different time, temperature and concentrations. A dynamic flow system was designed for this state. A scaled copper alloy pipes from the main hot water lines (heat exchanger) was used. Hexamine was used as corrosion inhibitor.The research involved a study of effect of the time ,temperature and acid concentration of each acid on the scale removal, and a comparison of the performance of the two used acids were investigated.